2012
DOI: 10.1185/03007995.2012.695730
|View full text |Cite
|
Sign up to set email alerts
|

Switching to biphasic insulin aspart 30/50/70 from biphasic human insulin 30/50 in patients with type 2 diabetes in normal clinical practice: observational study results

Abstract: Patients with long-standing type 2 diabetes can switch safely from BHI to BIAsp therapy, even if they receive intensified treatment, and they have no problems changing the timing of their insulin injections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…Studies published since the prior review have confirmed using continuous glucose monitoring that BIAsp 30 has a more favorable PD effect than BHI 30 [ 2 ] and fewer glucose fluctuations than a basal–bolus regimen [ 3 ]. Results from the large, prospective, multinational A 1 chieve study have expanded on results from previously reported RCTs and have shown that patients in real-life clinical practice using BHI 30 can realize clinical benefit from switching to BIAsp 30 [ 15 , 17 ] as well as improvements in quality of life [ 15 , 16 ]. Also consistent with previous work are several studies demonstrating that BIAsp 30 is safe and effective when used in insulin-naïve patients in primary care practice [ 7 9 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies published since the prior review have confirmed using continuous glucose monitoring that BIAsp 30 has a more favorable PD effect than BHI 30 [ 2 ] and fewer glucose fluctuations than a basal–bolus regimen [ 3 ]. Results from the large, prospective, multinational A 1 chieve study have expanded on results from previously reported RCTs and have shown that patients in real-life clinical practice using BHI 30 can realize clinical benefit from switching to BIAsp 30 [ 15 , 17 ] as well as improvements in quality of life [ 15 , 16 ]. Also consistent with previous work are several studies demonstrating that BIAsp 30 is safe and effective when used in insulin-naïve patients in primary care practice [ 7 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another observational study in Belgium and Luxembourg followed 592 patients at 12 and 26 weeks after switching from BHI 30 to BIAsp 30, BIAsp 50, or BIAsp 70 [ 17 ]. About two-thirds of patients took BIAsp 30 and one-third BIAsp 50, with few patients using BIAsp 70.…”
Section: Initiating Insulin Therapy With Biasp 30mentioning
confidence: 99%
“…[ 14 15 ] Significant improvements in mean HbA 1c were also noted in patients who switched from BHI 30 or 50 to BIAsp 30, 50 or 70 in routine clinical practice in another 26 weeks observational study. [ 16 ]…”
Section: Discussionmentioning
confidence: 99%
“…This observational trial suggests patterns of prescription premixed insulin that would be appropriate for an average practice. [ 11 ]…”
Section: Linical D Atamentioning
confidence: 99%